Certain results of Aleph-Function based on natural transform of fractional order - Pathak, Aarti; Mishra, Rajshree; Jain, DK; Ahmad, Farooq; Bhat, Altaf Ahmad (Annals of Mathematics and Physics, 2023)
In this research article, a new type of fractional integral transform namely the N-transform of fractional order is proposed, and derived a number of useful results of a more generalized function (Aleph-function) of fractional calculus by making use of the N-transform of fractional order. Further, the relation between it and other fractional transforms is given and some special cases have also been discussed.